2005
DOI: 10.1002/cncr.21087
|View full text |Cite
|
Sign up to set email alerts
|

Distribution according to histologic type and outcome by gender and age group in Taiwanese patients with lung carcinoma

Abstract: Objective To determine whether manual therapy or pulsed shortwave diathermy, in addition to advice and exercise, provide better clinical outcome at 6 months than advice and exercise alone in primary care patients with nonspecific neck disorders. Methods This was a multicenter, 3‐arm randomized controlled trial in 15 physical therapy departments. Of the 735 screened patients, 350 were recruited to the study (mean age 51 years) from July 2000 to June 2002. Participants were randomized to advice and exercise plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 114 publications
(100 reference statements)
3
53
4
Order By: Relevance
“…34 We have also found a low prevalence of ever smokers among female lung cancer patients in our previous study. 4 The cause for the very low prevalence rate of ever smoking in female lung cancer patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 We have also found a low prevalence of ever smokers among female lung cancer patients in our previous study. 4 The cause for the very low prevalence rate of ever smoking in female lung cancer patients remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2] Although tobacco smoking is a well-established etiologic factor for lung cancer, 3 we found that most of the female lung cancer patients in Taiwan were nonsmokers. 4 Lung cancer in Chinese women has different clinicopathological features compared with the Western population. The female to male ratio of lung cancer patients was higher than the average ratio worldwide, 4,5 and the cause remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reports implicating the estrogen signaling pathway in lung cancer (Marquez-Garban et al, 2007), and clear sex differences exist in lung cancer type and survival (Belani et al, 2007;Chen et al, 2005;Fu et al, 2005;Patel, 2005;Thomas et al, 2005). In particular, women who do not smoke are more susceptible to developing adenocarcinoma, a cancer type that derives from PTII cells expressing AR.…”
Section: Ar and Lung Cancermentioning
confidence: 99%
“…Female patients show better survival rates than males at any stage of the disease (Fu et al, 2005). Histological subtypes of the disease in women include proportionally more adenocarcinoma and less squamous cell carcinoma than men (Chen et al, 2005;Fu et al, 2005). Overall, men appear to have a higher rate of fatal outcome of lung cancer, but tend to be less vulnerable to tobacco carcinogens than women (International Early Lung Cancer Action Program Investigators et al, 2006).…”
Section: Introductionmentioning
confidence: 99%